2016
DOI: 10.1038/bjc.2016.263
|View full text |Cite
|
Sign up to set email alerts
|

MEK inhibition abrogates sunitinib resistance in a renal cell carcinoma patient-derived xenograft model

Abstract: Background:Renal cell carcinoma (RCC) patients treated with tyrosine kinase inhibitors (TKI) typically respond initially, but usually develop resistance to therapy. We utilised transcriptome analysis to identify gene expression changes during development of sunitinib resistance in a RCC patient-derived xenograft (PDX) model.Methods:RCC tumours were harvested during pre-treatment, response and escape phases. Direct anti-proliferative effects of sunitinib plus MEK inhibitor were assessed. Activation status (phos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 39 publications
(42 reference statements)
4
26
0
Order By: Relevance
“…These findings support the crucial role of mek1 kinase may be useful in cancer cells response to antiangiogenic agents. It was previously reported that inhibition of mek1 in the renal cell carcinoma xenograft model with acquired resistance to sunitinib successfully improved anti-tumor drug efficacy [ 47 ]. Therefore, targeting mek1 may be a promising pathway in treating TKI-resistant papillary renal cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…These findings support the crucial role of mek1 kinase may be useful in cancer cells response to antiangiogenic agents. It was previously reported that inhibition of mek1 in the renal cell carcinoma xenograft model with acquired resistance to sunitinib successfully improved anti-tumor drug efficacy [ 47 ]. Therefore, targeting mek1 may be a promising pathway in treating TKI-resistant papillary renal cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, angiogenesis inhibition may be a viable treatment approach for the highly vascular tumor types, such as ovarian cancer, lung cancer and breast cancer [5][6][7]. However, targeting single factor may produce drug resistance and compensatory angiogenesis because the roles of other factors may be strengthened [8]. Several inhibitors of growth factor, receptor and kinases such as Bevacizumab, Ramucirumab, Aflibercept, Sunitinib, Sorafenib, and Pazopanib have been brought to clinical treatment for malignant tumors but most of these approaches are based on the physiological effects of single pathway, which may be insufficient to induce enduring anti-tumor efficacy [9].…”
Section: Introductionmentioning
confidence: 99%
“…We searched the Gene Expression Omnibus(GEO) database, identified the following 2 sets of microarray data regarding renal cell carcinoma resistance to RTK inhibitors, and included these data in our study: GSE76068 [ 22 ] and GSE64052 [ 23 ]. In GSE76068, researchers implanted 8 RCC patient-derived xenografts in mice and then treated these mice with sunitinib for approximately 4 weeks, at which time drug resistance developed.…”
Section: Resultsmentioning
confidence: 99%